Role extraction, dynamics, and optimisation on networks - Tian, Y (2022)
Understanding the relationships between products is an important problem in industry, where two central concepts are complements and substitutes. Complementary products are sold separately but used together, each creating a demand for the other, while substitute products can be used in place of each other, each taking a demand from the other. Hence, such two competing product relationships are also essential in further understanding how the demand change of some products transforms into the change of the whole range of products.